LKB1 regulates PRMT5 activity in breast cancer. Issue 3 (31st October 2018) - Lattouf, Hanine; Kassem, Loay; Jacquemetton, Julien; Choucair, Ali; Poulard, Coralie; Trédan, Olivier; Corbo, Laura; Diab‐Assaf, Mona; Hussein, Nader; Treilleux, Isabelle; Le Romancer, Muriel
Abstract : Protein arginine methyltransferase 5 (PRMT5) is the main enzyme responsible for the symmetrical dimethylation of arginine residues on target proteins in both the cytoplasm and the nucleus. Though its activity has been associated with tumor progression in various cancers, the expression pattern of this oncoprotein has been scarcely studied in breast cancer. In the current work, we analyzed its expression in a large cohort of breast cancer patients, revealing higher nuclear PRMT5 levels in ERα‐positive tumors and an association with prolonged disease free and overall survival. Interestingly, high PRMT5 nuclear expression was also associated with higher nuclear liver kinase B1 (LKB1), suggesting that a functional relationship may occur. Consistently, several approaches provided evidence that PRMT5 and LKB1 interact directly in the cytoplasm of mammary epithelial cells. Moreover, although PRMT5 is not able to methylate LKB1, we found that PRMT5 is a bona fade substrate for LKB1. We identified T132, 139 and 144 residues, located in the TIM‐Barrel domain of PRMT5, as target sites for LKB1 phosphorylation. The point mutation of PRMT5 T139/144 to A139/144 drastically decreased its methyltransferase activity, due probably to the loss of its interaction with regulatory proteins such as MEP50, pICln and RiOK1. In addition, modulation of LKB1 expression modified PRMT5 activity, highlighting a new regulatory mechanism that could have clinical implications. Abstract : What's new? The arginine methyltransferase PRMT5 is associated with tumor progression in various cancers; however, its expression in breast cancer remains understudied. Here, the authors found that, as in prostate cancer, PRMT5 nuclear localization may have protective effects. Indeed, its expression is associated with higher patient survival. In addition, two threonine residues essential to PRMT5 enzymatic activity were identified. Interestingly, the tumor suppressor LKB1 a master kinase that regulates cell polarity, energy metabolism, and mTOR signaling phosphorylates PRMT5 on these residues, thereby decreasing the methyltransferase activity of PRMT5. These results highlight new opportunities to measure and target PRMT5 activity in breast cancer.